Invasive infections due to filamentous fungi other than Aspergillus: epidemiology and determinants of mortality. (May 2015) - Slavin, M.; van Hal, S.; Sorrell, T.C.; Lee, A.; Marriott, D.J.; Daveson, K.; Kennedy, K.; Hajkowicz, K.; Halliday, C.; Athan, E.; Bak, N.; Cheong, E.; et al.
Abstract: The epidemiology of invasive fungal disease (IFD) due to filamentous fungi other than Aspergillus may be changing. We analysed clinical, microbiological and outcome data in Australian patients to determine the predisposing factors and identify determinants of mortality. Proven and probable non- Aspergillus mould infections (defined according to modified European Organization for Research and Treatment of Cancer/Mycoses Study Group criteria) from 2004 to 2012 were evaluated in a multicentre study. Variables associated with infection and mortality were determined. Of 162 episodes of non- Aspergillus IFD, 145 (89.5%) were proven infections and 17 (10.5%) were probable infections. The pathogens included 29 fungal species/species complexes; mucormycetes (45.7%) and Scedosporium species (33.3%) were most common. The commonest comorbidities were haematological malignancies (HMs) (46.3%) diabetes mellitus (23.5%), and chronic pulmonary disease (16%); antecedent trauma was present in 21% of cases. Twenty-five (15.4%) patients had no immunocompromised status or comorbidity, and were more likely to have acquired infection following major trauma (p <0.01); 61 (37.7%) of cases affected patients without HMs or transplantation. Antifungal therapy was administered to 93.2% of patients (median 68 days, interquartile range 19–275), and adjunctive surgery was performed in 58.6%. The all-cause 90-day mortality was 44.4%; HMs and intensive-care admission were the strongest predictors of death (both p <0.001). Survival varied by fungal group, with the risk of death being significantly lower in patients with dematiaceous mould infections than in patients with other non- Aspergillus mould infections. Non- Aspergillus IFD affected diverse patient groups, including non-immunocompromised hosts and those outside traditional risk groups; therefore, definitions of IFD in these patients are required. Given the high mortality, increased recognition of infections and accurate identification of the causative agent are required.